Analysis of performance in English women`s domestic Twenty20 cricket - Haworth, G.; Mills, S. (International Journal of Performance Analysis in Sport, 2026)
Cricket has progressed over the years to adapt to crowd demands to increase levels of excitement, hence the introduction of Twenty20 (T20) cricket. The purpose of this paper was to identify the key variables that impact winning and to investigate if there are differences between men`s and women`s cricket. Primary research collected match data from scorecards of all 26 games of an English women`s T20 regional competition. Independent t-tests and Cohen`s d-test of effect size (ES) indicated significant differences between the winning and losing teams. Innings run rate (ES 1.12), total number of boundaries (ES 0.90), total wickets taken (ES 0.88), fours scored (ES 0.85), run rate in powerplay and percentage of runs from boundaries (both ES 0.67) revealed to be most significant for success in the competition. Secondary analysis explored the effect of bowling line and length. Bowling short lengths resulted in more than expected wickets in powerplay overs, and 66% of fours were scored off full pitched deliveries. Although many of the key variables that contribute to success within women`s cricket were similar to men`s cricket, differences were evident. Further research on women`s cricket is therefore required to confirm whether these differences between genders persist across multiple studies.